Copper Homeostasis in Aspergillus nidulans Involves Coordinated Transporter Function, Expression and Cellular Dynamics - Antsotegi-Uskola, Martzel; Markina-Iñarrairaegui, Ane; Ugalde, Unai (Frontiers in Microbiology, 2020)
Copper ion homeostasis involves a finely tuned and complex multi-level response system. This study expands on various aspects of the system in the model filamentous fungus Aspergillus nidulans. An RNA-seq screen in standard growth and copper toxicity conditions revealed expression changes in key copper response elements, providing an insight into their coordinated functions. The same study allowed for the deeper characterization of the two high-affinity copper transporters: AnCtrA and AnCtrC. In mild copper deficiency conditions, the null mutant of AnctrC resulted in secondary level copper limitation effects, while deletion of AnctrA resulted in primary level copper limitation effects under extreme copper scarcity conditions. Each transporter followed a characteristic expression and cellular localization pattern. Although both proteins partially localized at the plasma membrane, AnCtrC was visible at membranes that resembled the ER, whilst a substantial pool of AnCtrA accumulated in vesicular structures resembling endosomes. Altogether, our results support the view that AnCtrC plays a major role in covering the nutritional copper requirements and AnCtrA acts as a specific transporter for extreme copper deficiency scenarios.